2017
DOI: 10.1158/0008-5472.can-16-1731
|View full text |Cite
|
Sign up to set email alerts
|

mda-7/IL-24 Mediates Cancer Cell–Specific Death via Regulation of miR-221 and the Beclin-1 Axis

Abstract: Melanoma differentiation associated gene-7/Interleukin-24 (mda-7/IL-24) displays broad-spectrum anti-cancer activity in vitro, in vivo in preclinical animal models, and in a phase I/II clinical trial in patients with advanced cancers without harming normal cells or tissues. Here we demonstrate that mda-7/IL-24 regulates a specific subset of miRNAs, including cancer-associated miR-221. Either ectopic expression of mda-7/IL-24 or treatment with recombinant His-MDA-7 protein resulted in downregulation of miR-221 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 49 publications
(62 reference statements)
4
59
0
Order By: Relevance
“…IL‐24 was also found to be regulated by miR‐203 but the type of miR‐203 was not mentioned . In another report, it was shown that IL‐24 regulates miR‐221 expression in cancer cells . In this study, we identified that IL‐24 was regulated by miR‐203a‐3p.1 in HCC cells.…”
Section: Discussionmentioning
confidence: 60%
“…IL‐24 was also found to be regulated by miR‐203 but the type of miR‐203 was not mentioned . In another report, it was shown that IL‐24 regulates miR‐221 expression in cancer cells . In this study, we identified that IL‐24 was regulated by miR‐203a‐3p.1 in HCC cells.…”
Section: Discussionmentioning
confidence: 60%
“…MiR-221 has been considered to act as a tumor regulator [26,27]. In recent years, studies have found that miR-221 is associated with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study from our group demonstrates that overexpression of mda‐7/IL‐24 , either via Ad. or as a recombinant protein, downregulates miR‐221 and upregulates p27 and PUMA, resulting in cancer cell death (Pradhan et al, ). This study also identified beclin‐1 as a new transcriptional target of miR‐221 and showed that mda‐7/IL‐24 regulates autophagy through miR‐221/beclin‐1 feedback (Pradhan et al, ).…”
Section: Mda‐7/il‐24: Novel Multifunctional Cancer Therapeutic Cytokinementioning
confidence: 99%